Endurance exercise performance in masters runners: physiological determinants and training recommendations - Pugliese, L.; Pavei, Porcelli, S.; Marzorati, M.; Bonato, M.; La Torre, A. (New Studies in Athletics, 2015)
Masters athletes are typically characterised as middle-aged and older men and women who continue physical training and sport activities at different levels throughout life. However, regardless of training, a decline in peak athletic performance usually occurs with ageing. In endurance exercise the reduction of performance and its physiological determinants appear to be mediated in large part by a reduction in the exercise training 'stimulus'. This reduction is mainly a result of increased work and family commitments, the inability to follow structured training programmes, increased prevalence of exercise training-associated injuries contributing to reduced training intensity and volume. These concerns highlight the importance for choosing and administering an adequate training stimulus in order to achieve maximum results in the shortest available time for training. Therefore, the first part of this article analyses the factors responsible for the decrease in performance with increased age. It is followed by a presentation different training methodologies that Masters runners in the middle- to long-distance events can use in order to prevent this decrease and, more importantly, increase their performance.